Hydrothermal evolution of granitoid-hosted gold mineralization in gidami area: An example for orogenic-gold deposits in Egypt. (October 2018) - Abd El Monsef, Mohamed; Slobodník, Marek; Salem, Ibrahim A.
Abstract: The Gidami gold ore is a unique form for the orogenic-gold deposits in Egypt. The gold lode is found in the form of auriferous quartz veins and aplitic dikes, cut through hosting granitic rocks and probably extend into the neighbor metavolcanic rocks. The geochemical data revealed that the granitic rocks are of tonalite-granodiorite composition, show calc-alkaline nature and related to active continental margin (syn-orogenic). The ore body is controlled by NNW trending shear/fault zones, occupying fracture zones and fissures and dipping generally to East direction. Microscopic examination accompanied with Electron Microprobe Analyses revealed that, the existed sulfide minerals are (pyrite, sphalerite, chalcopyrite, molybdenite, pyrrhotite, covellite, Galena, and pentlandite). Ilmenite and goethite are the main oxide minerals. Native gold commonly occurs as small inclusions within pyrite and goethite, and also detected as tiny grains scattered within quartz vein (near the sulfides). Well-developed alteration zones occur associated with auriferous quartz veins; two types of wallrock alteration are distinguished: a) Inner (phyllic) alteration zone, and b) Outer (carbonatized) alteration zone. The outer alteration zone always exhibits higher gold content than the inner zone. Three types of fluid inclusions are recognized at the core and rim of the auriferous quartz vein as follows: 1) Two phases aqueous (H2 O-NaCl ± KCl), 2) Two phases aqueous (H2 ONaCl ± MgCl2 ), and 3) Three phases aqueous-carbonic (H2 O–NaCl-CO2 ±CH4 ) fluid inclusions. Isochores intersection from fluid inclusions data outlines that, the Gidami gold deposits are of the mesothermal type formed at temperatures range between (270–300 °C), and pressure (750–850 bar) corresponds to a depth around 3 km (assuming pure lithostatic pressure). The ore-bearing fluids are supposed to be sourced mainly by fluids of metamorphic and meteoric origin. However, criteria of partial mixing with water of magmatic signatures has been proposed during fluid evolution. The transportation of gold was in form of bisulphide compounds in moderately reduced, neutral to weakly alkaline environment and then the precipitation occurred as a result of changing in Eh and pH conditions. Highlights: The hosting granitic rocks are of tonalite-granodiorite composition, show calc-alkaline nature and related to active continental margin (syn-orogenic). Wallrock alterations are represented by an inner (phyllic) zone and an outer (carbonatized) zone. Gidami gold deposits are of mesothermal type formed at temperatures between (270–300 °C) and pressure (750–850 bars) corresponding to depth of around 3 km. Mixing between magmatic-metamorphic-meteoric waters has been suggested as a source for the ore-bearing fluids.